2018
DOI: 10.4088/jcp.16m11312
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and Dementia

Abstract: Herpes zoster was associated with an increased risk of dementia, independent of potential confounding factors. Antiviral treatment might be protective in preventing dementia in patients with herpes zoster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 0 publications
3
85
1
Order By: Relevance
“…In the second article, by Chen et al ( 2018 ), 39,205 patients with HZV, age range 54–90, were diagnosed during the period 1997–2013 and were followed over an average period of 6.2 years. The incidence of dementia was compared with that of 39,205 controls (mean age of both groups was 63.5 years).…”
Section: Evidence From Population Epidemiological Studies For a Role mentioning
confidence: 99%
“…In the second article, by Chen et al ( 2018 ), 39,205 patients with HZV, age range 54–90, were diagnosed during the period 1997–2013 and were followed over an average period of 6.2 years. The incidence of dementia was compared with that of 39,205 controls (mean age of both groups was 63.5 years).…”
Section: Evidence From Population Epidemiological Studies For a Role mentioning
confidence: 99%
“…Subsequently, it was shown that HSV-1 infection of cultured neurons and glia and mouse brain can increase the production of Aβ [177], and induce cytoskeletal abnormalities in neurons that include tau hyperphosphorylation [178]. Recent works have indicated that Aβ has antimicrobial properties against bacteria and viruses [179,180], and have substantiated the associations of herpes virus infections and AD or dementia [181,182,183,184,185]. These findings suggest that Aβ and/or tau may be protective responses to CNS infections that would be more likely to occur with age-associated immunosenescence and a dysfunctional BBB.…”
Section: The Bbb In Age-associated Neurological Diseasesmentioning
confidence: 99%
“…Moreover, two retrospective cohort studies demonstrated that HSV infection significantly increased the risk of developing all-cause dementia. Of note is that this risk was almost eliminated in patients treated with antiherpetics ( Chen et al, 2018 ; Tzeng et al, 2018 ; Long and Holtzman, 2019 ).…”
Section: Introductionmentioning
confidence: 99%